Southeast Asian Affairs 2022 - Daljit Singh; Hoang, Thi Ha; Khairulanwar Zaini (ISEAS Publishing, 2022)
Southeast Asian Affairs, first published in 1974, continues today to be required reading for not only scholars but the general public interested in in-depth analysis of critical cultural, economic and political issues in Southeast Asia. In this annual review of the region, renowned academics provide comprehensive and stimulating commentary that furthers understanding of not only the region's dynamism but also of its tensions and conflicts.